2017
DOI: 10.1007/s10047-017-0982-5
|View full text |Cite
|
Sign up to set email alerts
|

Veno–veno–arterial extracorporeal membrane oxygenation for acute respiratory distress syndrome with septic-induced cardiomyopathy due to severe pulmonary tuberculosis

Abstract: We describe the rare experience of veno-veno-arterial (VVA) extracorporeal membrane oxygenation (ECMO) in a patient with acute respiratory distress syndrome and septic-induced cardiomyopathy due to pulmonary tuberculosis (TB). A 24-year-old male patient who developed septic-induced cardiomyopathy secondary to pulmonary TB was administered veno-arterial (VA) ECMO for cardiac support. Six days later, the ECMO configuration mode was changed from VA to VVA to improve hypoxemia of the upper body and to prevent furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Both are common and highly lethal and have significant negative effects on survivors [20]. Sepsis-induced ARDS has an estimated incidence of over 40% and is the leading cause of ARDS death [21]. ARDS is a life-threatening complication featured by diffuse alveolar damage [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both are common and highly lethal and have significant negative effects on survivors [20]. Sepsis-induced ARDS has an estimated incidence of over 40% and is the leading cause of ARDS death [21]. ARDS is a life-threatening complication featured by diffuse alveolar damage [22].…”
Section: Discussionmentioning
confidence: 99%
“…As a complex pathological process, ARDS is regulated by transcription factors as well as miRNA. A miRNA is a small endogenous non-coding RNA molecule that includes approximately [18][19][20][21][22][23][24] nucleotides. It usually complements sites in the 3' untranslated region of the target messenger RNA for inhibiting the expression of post-transcriptional gene [8].…”
Section: Introductionmentioning
confidence: 99%
“…In the present case, the pathophysiology of TB may be disseminated, since the onset of clinical symptoms, including dyspnea, was acute, and CT images of disease onset showed diffuse consolidation shadows in both lungs without focal signs at the initial stage. In addition, a report of patient with ARDS and septic-induced cardiomyopathy secondary to pulmonary TB with the veno-veno-arterial (VVA) ECMO indicated that blood gas exchange was recovered slowly, while cardiac function was recovered within 10 days from the initiation of VVA-ECMO and the patient weaned ECMO at 28 days [16]. This result inferred the difficulty of recovering the respiratory function for patient with TB if the lung destruction has been occurred [16].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a report of patient with ARDS and septic-induced cardiomyopathy secondary to pulmonary TB with the veno-veno-arterial (VVA) ECMO indicated that blood gas exchange was recovered slowly, while cardiac function was recovered within 10 days from the initiation of VVA-ECMO and the patient weaned ECMO at 28 days [16]. This result inferred the difficulty of recovering the respiratory function for patient with TB if the lung destruction has been occurred [16]. However, the present case had the less lung destruction.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that the survival was better when supported by ECPELLA system than ECMO support alone in 30-day mortality in patients with refractory cardiogenic shock [34]. In cases with advanced pulmonary congestion and pulmonary oxygenation disorders, the Veno-veno-arterial ECMO system is preferable to VA-ECMO to prevent hypoxic blood perfusion to the brain through Impella [35].…”
Section: Ecpella (Ecmo Plus Impella)mentioning
confidence: 99%